Pengaruh Pengelolaan Keuangan, Pengalaman Keuangan, Tingkat Pendidikan dan Pengetahuan Akuntansi terhadap Kinerja Manajerial UMKM Di Kabupaten Pemalang - Melda, Bethari Sherawaly; Irianto, Bambang Setyobudi; Ulfah, Permata; Pratiwi, Umi (Jurnal Riset Akuntansi Soedirman, 2025)
This study aims to determine the influence of financial management, financial experience, education level, and accounting knowledge of MSMEs in Pemalang Regency. The population in this study is MSME players in Pemalang Regency, Central Java Province. The sample selection in this study used purposive sampling, and there were 100 MSMEs. Based on the results of the study, it shows that: (1) financial management has a positive effect on the managerial performance of MSMEs; (2) Financial experience does not have a positive effect on the managerial performance of SMEs; (3) Educational level does not have a positive effect on the managerial performance of SMEs; (4) Accounting knowledge has a positive effect on the managerial performance of SMEs.